Routledge handbook of democratization - Haynes, Jeffrey (London Routledge, 2018)
This handbook provides a global overview of the process of democratization, with chapter-by-chapter discussion at the country and regional levels, examining the interaction between the domestic and external factors that affect the progression of countries from authoritarian to democratic rule.
Section 1: Democratisation: The regional picture 1. Central and Eastern Europe Paul Lewis 2. Central America John A. Booth 3. South America Anita Breuer 4. Sub-Saharan Africa Elke Zuern 5. The Middle East and North Africa Francesco Cavatorta 6. Central Asia Verena Fritz & Jonathan Wheatley 7. Democracy in South Asia: India and Pakistan-Parallel Pasts, Divergent Futures Farida Jalalzai 8. Southeast and East Asia Matthew Carlson Section 2: Democratisation and Governance 9. Measuring democratisation Edward LiPuma & Thoas A. Koelble 10. Democratic transitions Jay Ulfelder 11. Hybrid Regimes – A Social Foundations Approach Garry Rodan & Kanishka Jayauriya 12. ‘Deviant democracies’ Renske Doorenspleet 13. The Military Thomas Bruneau 14. Political parties Vicky Randall 15. Civil Society David Herbert 16. Social capital Bo Rothstein Section 3: Democratisation and International Relations 17. The third and fourth waves of democracy Fabrice Lehoucq 18. Democratic Conditionality Richard Youngs 19. The United Nations and Democratisation Aurel Croissant 20. The European Union and democratization Michelle Pace 21. The African Union and democratization Charles Manga Fombad 22. The Organisation of American States and Democratisation Monica Herz Section 4: ‘Democratisation and Development’ 23. Democratization, poverty, and inequality Gordon Crawford & Abdul-Gafaru Abdulai 24. Democratization and security Vincent Boudreau 25. Democratization and Human Rights: Convergence and Divergence David Beetham 26. Democratization and gender Wendy Stokes 27. Democratization and war Wolfgang Merkel 28. Democratization and conflict resolution Sonja Grimm
Includes bibliographical references and index
Keywords: Democratization